Pengaruh Struktur Modal, Ukuran Perusahaan, Likuiditas dan Pertumbuhan Laba terhadap Kualitas Laba pada Bank yang Terdaftar di Bursa Efek Indonesia - Hesti Agustina; Zati Rizka Fadhila (Yayasan Literasi Sains Indonesia, 2026)
Earnings quality is earnings that reflect actual performance and thus do not mislead stakeholders in decision-making. The purpose of this study is to analyze the influence of capital structure, company size, liquidity, and earnings growth on earnings quality. The population in this study was 42 banks listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, reporting their financial statements. A sample of 14 banks was obtained using purposive sampling. The analysis used in this study was multiple linear regression analysis with the assistance of IBM SPSS Statistics 26. The results of this study indicate that capital structure has a positive effect on earnings quality, company size has a positive effect on earnings quality, and earnings growth has a positive effect on earnings quality. Meanwhile, liquidity has no effect on earnings quality. Future researchers are advised to add other variables, such as corporate governance, credit risk, and dividend policy, to provide a more comprehensive picture of the factors influencing earnings quality. Furthermore, a longer research period would provide results that are more representative of the banking conditions in Indonesia.